2016
DOI: 10.1007/s00265-016-2176-1
|View full text |Cite
|
Sign up to set email alerts
|

Diet cues alter the development of predator recognition templates in tadpoles

Abstract: Recognising predators accurately is key to making fine-scale adjustments to behaviour that enhance survival and maximise overall fitness for prey. Prey incorporate information from specific predator features in order to recognise predators and the risk they pose. For olfactory cues, prey can use both predator odour and diet cues to recognise predators. The role of diet cues in predator recognition has only been tested when they provide information about risk and act as an unconditioned stimulus. Thus, it is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…Many of the studies reviewed here exposed prey to predator odours and diet cues simultaneously, and yet antipredator responses of prey to predator odours can differ when diet cues are present or absent (Mitchell et al, 2015(Mitchell et al, , 2016bRelyea, 2005, 2009;Stabell et al, 2003). While there are a growing number of studies showing innate predator recognition (Dalesman et al, 2006;DeSantis et al, 2013;Langerhans and DeWitt, 2002;Vilhunen and Hirvonen, 2003), many studies have shown that, when diet cues are controlled for, predator-naive prey do not display antipredator responses to predator odours.…”
Section: Which Cues Are Responsible?mentioning
confidence: 99%
“…Many of the studies reviewed here exposed prey to predator odours and diet cues simultaneously, and yet antipredator responses of prey to predator odours can differ when diet cues are present or absent (Mitchell et al, 2015(Mitchell et al, , 2016bRelyea, 2005, 2009;Stabell et al, 2003). While there are a growing number of studies showing innate predator recognition (Dalesman et al, 2006;DeSantis et al, 2013;Langerhans and DeWitt, 2002;Vilhunen and Hirvonen, 2003), many studies have shown that, when diet cues are controlled for, predator-naive prey do not display antipredator responses to predator odours.…”
Section: Which Cues Are Responsible?mentioning
confidence: 99%
“…These studies reliably showed an absence of a learned response in the control group exposed to water. Given the tadpoles' consistent response to alarm cues and given the fact that the control groups were not necessary for directly assessing the differences between experimental groups in my experiment, I used reduced control groups similar to Mitchell et al (2016). The use of reduced control groups was also useful for reducing the number of animals involved in the study as required by the law of the country in which the experiment took place.…”
Section: Behavioural Antipredator Responsementioning
confidence: 99%
“…Sample sizes of experiment 2 were as follow: alarm cues + fish/crayfish mixture: 48; control water + fish/crayfish mixture: 36. Several learning studies with this protocol showed not learned response in the control group Chivers et al, 2016;Ferrari et al, 2009a;Lucon-Xiccato et al, 2016;Lucon-Xiccato et al, 2017); thus, we used reduced control groups to minimise the number of wild animals necessary for the study (Mitchell et al, 2016). The tadpoles were exposed to the mixture for 1 h; then, tadpoles were moved into 16 holding pails (approx.…”
Section: Conditioning With Odour Mixturementioning
confidence: 99%
“…We moved each individual tadpole to a 0.5-L cup and left them to acclimate for 30 min. The bioassay used to measure antipredator responses is identical to that used in previously published studies on tadpole antipredator responses (Lucon-Xiccato et al, 2016;Lucon-Xiccato et al, 2017;Mitchell et al, 2016). In the predator recognition test, each subject was exposed to a single predator cue.…”
Section: Predator Recognition Testmentioning
confidence: 99%
See 1 more Smart Citation